2017
DOI: 10.1080/2000625x.2017.1373552
|View full text |Cite
|
Sign up to set email alerts
|

Is surgical debridement necessary in the diabetic foot treated with photodynamic therapy?

Abstract: Background: Diabetic patients are susceptible to developing foot ulcers with serious complications such as osteomyelitis and amputations. Treatment approaches are still empirical and the benefit of usual procedures such as surgical debridement has not been properly evaluated. Photodynamic Therapy (PDT) is a non-invasive and highly efficient method for the treatment of the diabetic foot, being able to eradicate the infection and to stimulate healing, decreasing considerably the amputation risk. In the day-to-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…For proof of the principle of the applicability of the Repuls7PDI, we tested two photosensitizers and three different microbial model systems. Phenothiazinium dyes, such as MB [4], are widely used in PDT, and applications range from the treatment of diabetic leg ulcers [22], of infected burn wounds [23] and antibacterial fabrics [24], to environmental applications such as the treatment of plant pathogens [16]. Our results using red light activation prove the photoantimicrobial activity of MB against all bacteria and fungi employed in this study.…”
Section: Discussionsupporting
confidence: 59%
“…For proof of the principle of the applicability of the Repuls7PDI, we tested two photosensitizers and three different microbial model systems. Phenothiazinium dyes, such as MB [4], are widely used in PDT, and applications range from the treatment of diabetic leg ulcers [22], of infected burn wounds [23] and antibacterial fabrics [24], to environmental applications such as the treatment of plant pathogens [16]. Our results using red light activation prove the photoantimicrobial activity of MB against all bacteria and fungi employed in this study.…”
Section: Discussionsupporting
confidence: 59%
“…The use of aPDT is well documented for many diseases and conditions such as infected leg ulcers, 20 diabetic foot, 21 and chronic skin ulcers. 22 With specific regard to the oral environment, its action includes the treatment of leukoplakia, 17 lichen planus, 23 periodontal pockets, 24 peri-implantitis, 25 and oral decontamination as well.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all photosensitizers show photodynamic activity against gram‐positive bacteria, but activity against gram‐negative bacteria is limited to certain cationic photosensitizers. A few small published studies of low quality have reported that PDT lowered bacterial load, cured infections, and may have helped reduce lower extremity amputations . While PDT appears to be safe and well tolerated, commercial products are not yet available in most countries, and it is unclear if using PDT without systemic antibiotic therapy will be possible for most patients.…”
Section: Treatmentmentioning
confidence: 99%
“…A few small published studies of low quality have reported that PDT lowered bacterial load, cured infections, and may have helped reduce lower extremity amputations. [194][195][196][197] While PDT appears to be safe and well tolerated, commercial products are not yet available in most countries, and it is unclear if using PDT without systemic antibiotic therapy will be possible for most patients.…”
Section: Recommendation 27mentioning
confidence: 99%